Quality of Life of Patients six Months after Ischemic Stroke - Ada Sánchez Lozano; Raimel PandoTorres; José Luis de la Maza Martínez; Georgina González Alba; Ernesto Julio Bernal Valladares; Ada Lozano Leblanc (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Introduction: the quality scale of life for stroke may offer a more detailed information and on the total recovery of the patient, besides a more significant evaluation from his perspective. Objective: to determine the quality of life of the patients with ischemic stroke six months after their discharge. Methods: a cross descriptive study was developed in 123 patients with the clinical and/or imaging diagnosis of a first ischemic stroke, admitted in the stroke unit at the University General Hospital Dr. Gustavo Aldereguía Lima Cienfuegos, in the period between November 1st 2015 and October 31st 2016. The variables analyzed were: demographic (age, sex, origin, and labor relationship), related with the event (type of brain infarction and rehabilitation treatment). The descriptive procedure was done through central measure trends and percentages. Results: the male sex predominated with an average age of 69,29 years. The 84,6 % of the patients received rehabilitation treatment, those presenting a lower punctuation from the scale media of the quality of life for stroke. From the 31 patients with labor relationship 27 could return to work with an average punctuation of 12,07 in that scale. The 53,6 % from presented mild involvement of the quality of life and only and only 4,9 % classified as a severe involvement. Conclusion: mild involvement of quality of life predominated. The most affected areas were: emotions, socio-familiar functioning and cognition.